Empirical and Computational Support for Context-Dependent Representations of Serial Order: Reply to Bowers, Damian, and Davis (2009) - Botvinick, Matthew M.; Plaut, David C. (Psychological Review, 2009)
J. S. Bowers, M. F. Damian, and C. J. Davis (2009) critiqued the computational model of serial order memory put forth in M. Botvinick and D. C. Plaut (2006), purporting to show that the model does not generalize in a way that people do. They attributed this supposed failure to the model's dependence on context-dependent representations, translating this argument into a general critique of all parallel distributed processing models. The authors reply here, addressing both Bowers et al.'s criticisms of the Botvinick and Plaut model and the former's assessment of parallel distributed processing models in general. Reprinted by permission of the publisher.